Care transition of trauma patients: Processes with articulation work before and after handoff. (January 2022) - Wooldridge, Abigail R.; Carayon, Pascale; Hoonakker, Peter; Hose, Bat-Zion; Schroeer, Katherine; Brazelton, Tom; Eithun, Ben; Rusy, Deborah; Ross, Joshua; Kohler, Jonathan; Kelly, Michelle M.; Dean, Shannon; et al.
Abstract: While care transitions influence quality of care, less work studies transitions between hospital units. We studied care transitions from the operating room (OR) to pediatric and adult intensive critical care units (ICU) using Systems Engineering Initiative for Patient Safety (SEIPS)-based process modeling. We interviewed twenty-nine physicians (surgery, anesthesia, pediatric critical care) and nurses (OR, ICU) and administered the AHRQ Hospital Survey on Patient Safety Culture items about handoffs, care transitions and teamwork. Care transitions are complex, spatio-temporal processes and involve work during the transition (i.e., handoff and transport) and preparation and follow up activities (i.e., articulation work). Physicians defined the transition as starting earlier and ending later than nurses. Clinicians in the OR to adult ICU transition without a team handoff reported significantly less information loss and better cooperation, despite positive interview data. A team handoff and supporting articulation work should increase awareness, improving quality and safety of care transitions. Highlights: SEIPS-based process modeling applies to higher complexity processes. Articulation work can be highlighted with SEIPS-based process modeling. Articulation work outside of handoffs is necessary for safe care transitions. Team handoffs increased team members' awareness of poor cooperation. Physicians and nurses think of care transition scope differently.